Evaluating the effectiveness of styles of play in elite soccer - Fernandez-Navarro, J.; Fradua, L.; Zubillaga, A. (International Journal of Sports Science & Coaching, 2019)
The aim of this study was to evaluate the effectiveness of styles of play in soccer and the influence of contextual variables (i.e. match status, venue and quality of opposition). Team possessions (n = 68,766) from the 380 matches of the 2015-2016 English Premier League season were collected for this study. The Possession Effectiveness Index, based on Expected Goals and Ball Movement Points metrics, was used to measure the effectiveness of team possessions. Linear mixed models were applied to analyse the influence of contextual variables on the effectiveness score for each style. Results showed that the effectiveness of Direct Play, Counterattack, Maintenance and Crossing significantly increased when teams were winning by two or more goals. Counterattack increased its effectiveness when teams were winning by one goal and reduced its effectiveness when losing by one goal. The effectiveness of Direct Play increased when losing by two goals or more. Playing away negatively affected the effectiveness of Direct Play, Maintenance and High Pressure. In addition, playing against a stronger opposition reduced the effectiveness of all styles of play. The results suggest that the effectiveness of styles of play changes under specific circumstances and that not all contextual variables affect them in the same way.